2021
DOI: 10.3390/ph14111159
|View full text |Cite
|
Sign up to set email alerts
|

Original Contributions to the Chemical Composition, Microbicidal, Virulence-Arresting and Antibiotic-Enhancing Activity of Essential Oils from Four Coniferous Species

Abstract: This study aimed to establish the essential oil (EO) composition from young shoots of Picea abies, Larix decidua, Pseudotsuga menziesii, and Pinus nigra harvested from Romania and evaluate their antimicrobial and anti-virulence activity, as well as potential synergies with currently used antibiotics. The samples’ EO average content varied between 0.62% and 1.02% (mL/100 g plant). The mono- and sesquiterpene hydrocarbons were dominant in the composition of the studied EOs. The antimicrobial activity revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 60 publications
1
23
1
Order By: Relevance
“…Gymnosperms and, in particular, conifers produce EOs characterized by compounds belonging to the family of terpenes such as monoterpenes, sesquiterpenes, and their derivatives [ 18 ]. In agreement with previous works [ 19 , 20 , 21 , 22 ], our results showed monoterpenes prevail over sesquiterpenes. In particular, the two major components of J. communis and L. decidua EOs were α -pinene or sabinene, which were also found in other Juniperus [ 23 , 24 ] and Larix species [ 17 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Gymnosperms and, in particular, conifers produce EOs characterized by compounds belonging to the family of terpenes such as monoterpenes, sesquiterpenes, and their derivatives [ 18 ]. In agreement with previous works [ 19 , 20 , 21 , 22 ], our results showed monoterpenes prevail over sesquiterpenes. In particular, the two major components of J. communis and L. decidua EOs were α -pinene or sabinene, which were also found in other Juniperus [ 23 , 24 ] and Larix species [ 17 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…EOs from conifer leaves have been reported to have high therapeutic potential [ 48 ] and, therefore, they are widely used in the treatment of infections and inflammatory phenomena [ 49 ]. Several studies demonstrated their biological properties [ 20 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], including allelopathic effects [ 10 , 11 ]. Nevertheless, EOs obtained from Juniperus and Larix species have been rather neglected from this point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy employing both essential oils and classic antibiotics has proven effective in preventing the development of resistant strains and improving therapy efficiency [ 15 , 16 ]. Therefore, the combined effect of MNEO with conventional antibiotics (chloramphenicol and streptomycin) against four pathogens was investigated by using a checkerboard microtiter assay [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…When such interactions result in synergistic effects, they can also be employed to improve therapy efficiency. Another benefit of such combinations is that lower doses are employed, which reduces side effects and treatment costs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, novel anti-biofilm strategies are urgently required to fight the associated infections and the negative impact of biofilm development in other fields of human activity [4]. Some medicinal plants and vegetal extracts, such as lavender, eucalyptus, and rosemary essential oils, show promising potential for treating biofilm-associated pathologies [5,6]. Many medicines also contain compounds isolated directly from plants or modified versions of natural products.…”
Section: Introductionmentioning
confidence: 99%